IGNITING AWARENESS TRANSFORMING ADOLESCENT KNOWLEDGE OF PCOS THROUGH STRUCTURED EDUCATION - Ms. Abizha. G; Ms. Jayamalli.N; Ms. Indhumathi; Ms. Hemalatha; Mr.Fairooz Haneefa (The Bioscan, 2026)
The study pre-test dealt with the perception of polycystic ovarian syndrome among adolescent girls. With the purpose of measuring the effectiveness of a structured training program to raise the level of knowledge about polycystic ovarian syndrome, a post-test was administered among teenage girls along with determination of demographic variables that characterize adolescent girls' perception of polycystic ovarian syndrome. It has been assumed in the research that the understanding of polycystic ovarian syndrome among nursing students significantly differs between the first and the second measurements. There is a crucial relationship between the demographic variables selected by nursing students and their knowledge of polycystic ovarian syndrome, both before and after the evaluation. The research applied a quantitative approach and a quasi-experimental descriptive design for its analysis. One hundred potential nursing students from SRM College of Nursing were selected for the study through an appropriate sampling method. All the studies were conducted in SRM College of Nursing, Kattankulathur. Data was collected over the duration of one week. Structured questionnaires were implemented to accumulate data. The data analysis was conducted using a combination of descriptive and inferential statistics. Among the teenage girls who took the pretest, the majority of the participants had 2(2%) “B+” grade of knowledge, 4(4%) had “B” grade of knowledge, 13(13%) had “c” grade of knowledge and 81(81%) had “D” grade of knowledge. In contrast, in the post test after the intervention 8(8%) had “A+” grade of knowledge, 11(11%) had “A” grade of knowledge,25(25%) had “B+” grade of knowledge, 32(32%) had “B” grade of knowledge, and 23(23%) had “C” grade of knowledge. The results of the study were that dysfunction of female sex hormones is present in patients with polycystic ovarian syndrome. It causes infertile, ovarian cysts, irregular menstruation, and numerous other health conditions. Preventive initiatives, such as awareness campaigns, will enhance adolescent girls' comprehension. The majority of adolescent females in this study had negative attitudes and limited comprehension regarding polycystic ovarian syndrome (PCOS) throughout the pretest. Following the systemic training, the knowledge implementation of the experimental group showed a tremendous increase. The findings were that in-depth training is one of the most effective ways to improve knowledge in the case of polycystic ovarian syndrome. The regulated educational programs are indeed possible, economical, and effortless. Keywords Igniting Awareness, transforming knowledge, polycystic ovarian syndrome, structured education and adolescent girls.